Screening for early warning of psychological crisis and intervention in children aged 8–18 years with cancer: a historical controlled trial - Yu, Lu; Mo, Lin; Liu, Yixuan; Huang, Xiaoyan (Frontiers in Pediatrics, 2023)
Background: Cancer is one of the main causes of death among children and adolescents. Several studies have shown that cancer can causes various psychological problems in children. These psychological problems will hinder children's development. The aim of this study was to establish a model of early warning intervention for children with cancer and explore its application effects. Methods: We recruited 345 children aged 8-18 years with cancer as the study participants. 173 children from December 2019 to March 2020 were selected as the control group, and 172 children from July 2020 to October 2020 were selected as the intervention group. Routine nursing model was adopted for control group and the early warning and intervention model was applied for intervention group. The DASS-21 scale was used to evaluate the psychological status of children with cancer before and 3 months after intervention. Results: Before intervention, there was no significant difference in the levels and incidence rate of depression, anxiety and stress between the control group and the experimental group. After intervention, the levels of depression, anxiety and stress in the experimental group (5.79±4.34, 4.91±3.98, 6.98±4.67) were lower than those in the control group (8.79±5.34, 9.91±6.53, 12.95±8.71), the incidence rate of depression, anxiety and stress in the experimental group (12.79%, 29.07%, 5.23%) were lower than those in the control group (46.82%, 49.71%, 27.17%), and the difference between the two groups was statistically significant (both P<0.05). Conclusions: children aged 8-18 years with cancer have obvious psychological problems, the psychological crisis early warning and intervention model can effectively improve the psychological problems of children with cancer.